APPLICATION OF THE DEVICE FOR MEASURING REACH HEIGHT AFTER A JUMP IN BIOMECHANICAL DIAGNOSTICS - Aceski, Aleksandar; Spasovska, Katerina; Daskalovski, Borce; Vuksanovikj, Vladimir (Faculty of physical education sport and health, Skopje, 2022)
The monitoring of legs power is an integral part of the training process of athletes for whom this motor ability is of great importance. The device for measuring reach height is practical and easy to use, which can be applied both in the laboratory and in field settings. The obtained results can serve as an indicator for monitoring the effect of the training process, the current level of legs power as well as the degree of fatigue of the athlete.
Keywords: muscle power, vertical jump, training, planning, biomechanics.